Perkiraan Angka Migrasi Neto Perkelompok Umur Provinsi Bali Tahun 2020 - Nima Kasina Auliarahman; Yayat Karyana (UNISBA Press, 2022)
Abstract. Population growth is influenced by three demographic components, namely mortality, fertility, and migration. The main motive for population migration is economic factors. The tourism sector in Bali Province is a driving force for the economy. The impact of the development of the tourism sector has increased economic activity in various sectors, including increasing job opportunities in the Province of Bali. The net migration rate, which is the difference between in-migration and out-migration, is another aspect of determining the growth rate of a region. In the ten years since 2010, the population of Bali has increased by 426.65 thousand people or an average of 42.66 thousand per year. In the 2020 Population Census, the population of Bali Province is 4,317,404 million people, the Population Growth Rates (LPP) of the Provinces of Bali and Indonesia are 1.01 percent and 1.25 percent, respectively (Central Bureau of Statistics, 2021). By knowing the population of the Province of Bali, the Population Growth Rate (LPP) of the Provinces of Bali and Indonesia, as well as the Age Specific Net Migration Rate (ASNMR), it can be calculated the number of net migrations, the number of net migrants per age group, and the net migration index in the Province of Bali in 2020. The result is that the number of net migration is 10,362 people, the Age Specific Net Migration Rate (ASNMR) for all age groups produces a negative net migration rate, and produces a negative Net Migration Index (IMN). Abstrak. Pertumbuhan penduduk dipengaruhi oleh tiga komponen demografi, yaitu mortalitas, fertilitas, dan migrasi. Motif utama terjadinya migrasi penduduk adalah faktor ekonomi. Sektor pariwisata di Provinsi Bali merupakan motor penggerak perekonomian. Dampak dari berkembangnya sektor pariwisata, aktivitas ekonomi diberbagai sektor meningkat, termasuk bertambahnya peluang kerja di Provinsi Bali. Tingkat migrasi neto yaitu selisih antara migrasi masuk dengan migrasi keluar merupakan aspek lain dari menentukan laju pertumbuhan suatu daerah. Dalam kurun waktu sepuluh tahun sejak tahun 2010, jumlah penduduk Bali mengalami penambahan sebesar 426,65 ribu jiwa atau rata-rata sebanyak 42,66 ribu per tahun. Pada Sensus Penduduk 2020 jumlah penduduk Provinsi Bali sebesar 4.317.404 juta jiwa, Laju Pertumbuhan Penduduk (LPP) Provinsi Bali dan Indonesia masing-masing sebesar 1,01 persen dan 1,25 persen (Badan Pusat Statistika, 2021). Dengan mengetahui jumlah penduduk Provinsi Bali, Laju Pertumbuhan Penduduk (LPP) Provinsi Bali dan Indonesia, serta Age Specific Net Migration Rate (ASNMR), maka dapat dihitung jumlah migrasi neto, angka migran neto perkelompok umur, dan indeks migrasi neto di Provinsi Bali tahun 2020. Hasilnya didapatkan jumlah migrasi neto sebanyak 10.362 orang, Age Specific Net Migration Rate (ASNMR) seluruh kelompok umur menghasilkan angka migrasi neto yang negatif, dan menghasilkan Indeks Migrasi Neto (IMN) yang negatif.